Periodic elastic nanodomains in ultrathin tetragonal-like BiFeO3 films - Luo, Zhenlin (2014)
We present a synchrotron grazing incidence x-ray diffraction analysis of the domain structure and polar symmetry of highly strained BiFeO3 (BFO) thin films grown on LaAlO3 substrate. We reveal the existence of periodic elastic nanodomains in the pure tetragonal-like BFO ultrathin films down to a thickness of 6 nm. A unique shear strain-accommodation mechanism is disclosed. We further demonstrate that the periodicity of the nanodomains increases with film thickness but deviates from the classical square root law in the ultrathin thickness regime (6–30 nm). Temperature-dependent experiments further reveal the disappearance of periodic modulation above ∼90 °C due to a MC-MA structural phase transition.